Effect of forced displacement on health - Ivan Zilic (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
This paper analyzes health consequences of forced civilian displacement that occurred during the War in Croatia 1991-1995 which accompanied the demise of Yugoslavia. Using the Croatian Adult Health Survey 2003 we test whether displacement is relevant in explaining various dimensions of measured and self assessed health. We adopt an instrumental variable approach where civilian casualties per county are used as an instrument for displacement. We find robust significant adverse effects on self assessed health, on probability of suffering from systolic and diastolic hypertension, and on mental health and role emotional SF-36 dimensions. We also address possible channels of adverse effect, and find that displacement did not induce a change in healthy behaviors, and that the negative effect of displacement is channeled through adverse economic conditions that the displaced individuals face.
Keywords: I10; O12; O15; 330; Conflict; Migration; Health